Produção e qualidade de sementes de quinoa em função do arranjo espacial - Oliveira Filho, Antonio Francelino de (2017)
The aim of this study was to evaluate the effect over two years of population arrangements on vegetative characteristics, production components and physiological potential in seeds of the quinoa ‘BRS Piabiru’. The experiments were carried out in the experimental area of the agriculture sector of the Department of Plant Science, Federal University of Ceará Pici Campus, in Fortaleza, Ceará, during the agricultural years 2014/2015 (from October to February) and 2015/2016 (from September to January). The treatments were the result of a 3 x 3 factorial scheme (row spacings: 20, 40 and 60 cm, and plant spacings within a row: 10, 15 and 20 cm), with the treatments distributed over four replications. Vegetative characteristics were evaluated by plant height, stem diameter, number of branches, specific leaf area, leaf area index and shoot dry weight. For the production characteristics, the panicle length, seed to panicle ratio, productivity, 1000-seed weight and seed oil content were evaluated. The physiological potential of the seeds was evaluated by tests of germination and vigour (percentage germination, germination speed index, mean germination time and accelerated ageing). The experiments were analysed jointly in relation to cycle for seed production and quality. Population arrangement and planting cycle interact on the vegetative characteristics and yield of the quinoa, with the combination of 20 x 10 cm producing around 10 ton.ha-1 shoot dry weight, and 1,162.12 kg.ha-1 seeds. The physiological quality of the seed is dependent on the density within the row, where spacings of 15 and 20 cm promote greater percentage germination (over 84%). An increase in planting density gives a reduction in panicle size of more than 18 cm for some combinations, but this is compensated for by an increase in seed productivity. The agricultural year affected seed quality within the various plant populations, which may be related to climatic factors.